Mother’s knowledge of nutrition is a risk factor of malnutrition in children under five years old in coastal areas of Kendari city - Juminten Saimin; Ahmad Fahmi Nugraha; Asmarani Dian Pertiwi; Ashaeryanto Ashaeryanto (Berita Kedokteran Masyarakat (BKM), 2019)
Objective: This study aimed to assess the risk of mother’s knowledge about nutrition to the incidence of malnutrition in children under five years old in coastal areas of Kendari City. Method: This study was observational analytic design with case control approach. The study was conducted in the coastal area of Kendari City, Southeast Sulawesi on November to December 2018. Case group was mother of children aged 6-59 months who experienced malnutrition in the working area of Abeli, Mata and Benu-Benua Health Center in October 2018. Control group was mother of children aged 6-59 months who did not experience malnutrition. Malnutrition was determined by measuring body weight and then adjusted to the category and threshold of nutritional status based on the body weight index according to age. There were 64 samples consisted of 16 case and 48 controls. Samples of case group were recruited using total sampling. Samples of control group were recruited using purposive sampling with non-matching method according to the inclusion and exclusion criteria. Mother's knowledge about nutrition was determined using the questionnaire. The Odd Ratio (OR) statistical test was used with a 2x2 contingency table and a 95% confidence level with a significance level of α = 0.05. Results: The majority of respondents were 36-45 years old in the case group (37.5%) and 26-35 years old in the control group (50.0%). The majority of education level was junior high school in the case group (43.7%) and high school in the control group (47.9%). The majority of mother's knowledge about nutrition was less in the case group (81.2%) and good knowledge in the control group (68.7%). The statistical test results were obtained OR = 9.533 (CI=95%) with Lower Limit (2.361) and Upper Limit (38.501).   Conclusion: Mother’s knowledge about nutrition is a risk factor for malnutrition in children aged 6-59 months in coastal areas of Kendari City. Mother’s knowledge of nutrition has a 9 times greater risk for malnutrition in children under five years old in coastal areas. Good knowledge of nutrition and malnutrition is needed to improve public health status.